Factors and Outcomes Associated with MRCP Use prior to ERCP in Patients at High Risk for Choledocholithiasis. (28th April 2016) - Anand, Gobind; Patel, Yuval A.; Yeh, Hsin-Chieh; Khashab, Mouen A.; Lennon, Anne Marie; Shin, Eun Ji; Canto, Marcia I.; Okolo, Patrick I.; Kalloo, Anthony N.; Singh, Vikesh K.
Abstract : Background . Consensus guidelines recommend that patients at high risk for choledocholithiasis undergo endoscopic retrograde cholangiopancreatography (ERCP) without additional imaging. This study evaluates factors and outcomes associated with performing magnetic resonance cholangiopancreatography (MRCP) prior to ERCP among patients at high risk for choledocholithiasis. Methods . An institutional administrative database was searched using diagnosis codes for choledocholithiasis, cholangitis, and acute pancreatitis and procedure codes for MRCP and ERCP. Patients categorized as high risk for choledocholithiasis were evaluated. Results . 224 patients classified as high risk, of whom 176 (79%) underwent ERCP only, while 48 (21%) underwent MRCP prior to ERCP. Patients undergoing MRCP experienced longer time to ERCP (72 hours versus 35 hours, p < 0.0001 ), longer length of stay (8 days versus 6 days, p = 0.02 ), higher hospital charges ( 23, 488 versus 19, 260, p = 0.08 ), and higher radiology charges ( 3, 385 versus 1, 711, p < 0.0001 ). The presence of common bile duct stone(s) on ultrasound was the only independent factor associated with less use of MRCP (OR 0.09, p < 0.0001 ). Conclusions . MRCP use prior to ERCP in patients at high risk for choledocholithiasis is common and associated with greater length of hospital stay, higher radiology charges, and a trend towards higher hospital charges.